AB0207 CLINICAL IMPACT OF ANTI-CARP ANTIBODIES IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Markovic, M.; Glisic, B.; Petronijevic, M.
Abstract : Background: Antibodies directed against carbamylated proteins (anti-CarP) have been recently introduced for the first time as a new biomarker in rheumatoid arthritis (RA) (1). Their presence is predictive for the development of RA (2). Anti-CarP antibodies are associated with the development of more severe forms of the disease in overall and anti-citrullinated peptide antibodies negative population of patients with RA (3). In the literature is still current the research which associate these antibodies with disease activity and functional status of patients. Objectives: This study investigated the incidence of anti-CarP positive findings in patients with RA on synthetic and biologic disease-modifying therapy (DMT) and the relationship between anti-CarP antibody status and both disability and disease activity. Methods: It was an open-label, observational, cross-sectional study. The trial included 70 patients with RA diagnosed on the basis of ACR 1987 and ACR / EULAR 2010 criteria, on treatment with synthetic and biological DMT, who attended the Clinic of Rheumatology, Military Medical Academy, from September to December 2018.The control group consisted of 18 healthy individuals. After approval of the institutional Ethical Committee and after patients have signed Informed Consent, the study was conducted. Disease activity score (DAS28) was determined for the assessment of RA activity, and the assessment of patients' functional ability was performed using the Health assessment questionnaire disability index (HAQ-DI). Concentration of anti-CarP antibodies was determined by commercial ELISA anti-CarP quantitative sandwich immunoassay. The methods of descriptive and analytical statistics were used in statistical data processing. Results: Based on the cut-off value (5.9 ng / ml), no one in the control group had positive anti-CarP antibodies, while 34.7% of the subjects with RA were positive. The positive correlation was found between anti-CarP antibody concentration and DAS28 in all RA patients (p = 0.0003; Pearson r = 0.4829). The positive correlation was also found between anti-CarP antibody concentration and HAQ-DI in all RA patients (p = 0.0003; Pearson r = 0.4253). Conclusion: Anti-CarP antibodies were present in a significant number of patients with RA. This study demonstrated that patients with RA with higher concentrations of anti-CarP antibodies have higher disease activity and impaired functional status. It is undisputed that further and larger studies are needed to better determine the clinical significance of these antibodies. References: [1]Shi J, Knevel R et al. Autoantibodies recognizing carbamylated proteins are present in sera of patients with rheumatoid arthritis and predict joint damage. Proc Natl AcadSci U S A. 2011 Oct 18;108(42):17372-7. [2]Yee A, Webb T et al. Anti-CarP antibodies as promising marker to measure joint damage and disease activity in patients with rheumatoid arthritis. Immunol Res. 2015 Feb;61(1-2):24-30. [3]Brink M, Verheul MK et al. Anti-carbamylated protein antibodies in thepresymptomatic phase of rheumatoid arthritis, their relationship with multiple anticitrulline peptide antibodies and association with radiological damage. Arthritis Res Ther. 2015 Feb 7;17:25. Disclosure of Interests: None declared